HIV-1 RNA Kinetics in Blood Plasma and in Seminal Plasma of Men Starting a Dolutegravir-Based Triple-Combination Regimen at the Time of Primary HIV-1 Infection. (24th June 2021) - Ghosn, Jade; Assoumou, Lambert; Lascoux-Combe, Caroline; Peytavin, Gilles; Amat, Karine; Gabassi, Audrey; Le, Minh P; Nzalakanda, Robert; Valin, Nadia; Landman, Roland; Chaix, Marie-Laure; Delaugerre, Constance
Abstract: We compared the proportion of participants achieving first undetectable HIV-1 RNA (VL) in seminal plasma (SP) and blood plasma (BP) in 19 men starting dolutegravir-based regimen at primary HIV infection. At baseline, median VL was 6.5 (interquartile range [IQR], 5.6–7.9) and 4.5 (IQR, 3.5–5.0) log10 copies/mL in BP and SP, respectively. Between baseline and week 48, significantly higher proportion of participants achieved first VL below limit of quantification in SP (93.0%) than in BP (84.2%; P = .008). Time to first undetectable VL was 8 weeks in SP (95% confidence interval [CI], 5.6–10.4) and 24 weeks in BP (95% CI, 14.1–33.9).